Evaluasi Program Pembelajaran Literasi Multibahasa di Sekolah Dasar - Komalasari, Lela; Hadisah, Lina (Buletin Ilmiah Pendidikan, 2022)
This research evaluates the effectiveness of the Multilingual Literacy Learning Program at Bagjasari 1 Elementary School (SD). Through an analysis of student responses, teacher experiences, and environmental factors, the study highlights the positive impact of the program on students' reading and writing abilities. Student responses indicate a significant improvement in academic participation and achievement, affirming the program's success in achieving learning objectives. Teachers emphasize the importance of collaboration among peers and support from school administration in program implementation, as well as the crucial role of environmental factors, such as support from the school community and the integration of local culture, in enhancing program effectiveness. Recommendations for future research include involving more schools in similar programs and refining multilingual learning strategies to meet the diverse learning needs of students. The research findings make a significant contribution to the development of education policies and teaching practices that are more responsive, with the aim of improving educational quality and ensuring equal access to education for all students.